Role of C-reactive Protein, Leucocyte and Neutrophil Count in Diagnosis of Acute Appendicitis (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Acute appendicitis is the most common cause of surgical acute abdomen and appendicectomy is the most commonly done surgery. Accurate preoperative diagnosis can reduce negative appendicectomy rate.Objective: To evaluate the diagnostic accuracy of C-reactive protein (CRP), total leucocyte count (TLC) and neutrophil count in patients operated after clinical diagnosis of acute appendicitis.Materials and Methods: This cross-sectional observational study was conducted among 100 patients at Combined Military Hospital, Dhaka from August 2012 to January 2013. Serum CRP level was measured by latex agglutination method which is a qualitative test and level of 6 mg / L was considered positive. TLC and neutrophil count were estimated by processing blood sample through automated haematology analyzer. TLC level of 10.5 x 109/L and differential count of neutrophil more than 75% were considered elevated.Results: Out of 100 cases the mean age of the patients was 21.7 years and 65 patients were male and 35 patients were female with male to female ratio 1.85:1. Majority cases (54%) were in the age group of 11-20 years. Clinical diagnosis was correct in 93% cases and negative appendicectomy rate was 07% (p